Predicação dirigida x predicação centrada: a (não) ocupação do lugar sintático de objeto na perspectiva da semântica da enunciação - Luciani Dalmaschio (2013)
This research is based on studies developed by the Semantics of Enunciation in order to propose an analytical work that is organized in a tone syntax based enunciative, whose theoretical assumption proposes that the linguistic functioning is governed by the plane of the forms and the plane of enunciation. In this approach, the focus of the analysis is on the syntactic place verbal object. This work, based on this grammatical topic and also in a diverse corpus, works with the proposition that the syntactic silence presents itself as a meaningful constitutive element, as well as occupation conditions are determined by general an specific enunciative forms. This study also discusses that verbal predications are divided both in oriented predications, which occurs when they are guided to an object, and centered predications, which are accomplished when the direction of meaning is guided to the verb. Besides, we propose a categorization of such predications by constructing a continuous. As to, this research is based on an amplitude of referential dominium that is established because of the possible occupations which are accomplished as to produce the effect of enunciative completion. In this sense, this work analyses the linguistic constitution of the object, the enunciative conditions for the occupation of this place, as well as the effect of meaning that this occupation (or the lack of it) provides.